The The Impact of Code Switching in Conversation of Ã¢â‚¬Å“Nebeng BoyÃ¢â‚¬Â Youtube Vlogs Towards Communication in English Among The Participants - Astani, Widi; Rukmini, Dwi; Sutopo, Djoko (Universitas Negeri Semarang, 2020)
The present study is aimed at investigating the impact of code switching realized in the conversation of Ã¢â‚¬Å“Nebeng BoyÃ¢â‚¬Â youtube vlog. This qualitative research is conducted by observing and analysing the conversations from four downloaded video as the data which then transcribed them in a written form. The data analysis also included the types and the functions of code switching which occurred in those four transcribed conversations in order to ease the researcher in determining the impact. The finding shows that intra-sentential code switching is the most frequent type and repetition is the most frequent function of code switching which occurred, and the impact is that the participants experienced language loss and language gain as the result of bilingualism through code switching. The English ability that is improving, results in the loss of Indonesian language ability. Bilingualism and oppression of using English language are external factors that also result code switching, which is then give impact to the loss of language that participants have learned before. The findings in this study indicated that three types of code-switching found in the conversations; inter-sentential code-switching (31.3%), intra-sentential code-switching (41.9%), and emblematic/ tag switching (26.8%). The participants also used code-switching for various functions. The most significant function was repetition which got the highest percentage (18.5%) among the other functions of code-switching in four transcribed conversations. It is also found that code-switching brought impact to the participants in term od language capabilities. It resulted in the loss of Indonesian language and the gain of English ability. The most significant factors that cause language loss and language gain were the bilingual settings they experienced and the oppression to use the English language in their daily life to communicate with others. An interesting phenomenon of code-switching that occurred in the bilingual community was shown in the analysis and findings. It is proven that the participants in this study performed code-switching as one of the strategies in communication. The existence of code-switching also open up a realistic view that by using alternative languages, it helps to reduce the gap of misunderstanding in a conversation, so that the intimacy or solidarity can be built among the participants